Criminal justice - Pennock, James Roland; Chapman, John Williams (Nomos, 1985)
Introduction / J. Ronald Pennock -- The moral and metaphysical sources of the criminal law / Michael S. Moore -- Intentionality and the concept of the person / Lawrence Rosen -- The deconstruction and reconstruction of intent / Martin Shapiro -- Classification-based sentencing : some conceptual and ethical problems / Hugo Adam Bedau -- How to make the punishment fit the crime / Michael Davis -- Retributivism and the state's interest in punishment / Jeffrie G. Murphy -- A motivational theory of excuses in the criminal law / R.B. Brandt -- Criminal responsibility in government / Dennis F. Thompson -- A comment on "Criminal responsibility in government" / Christopher D. Stone -- The legal and moral responsibility of organizations / Susan Wolf -- On economic theory of crime / Alvin K. Klevorick -- Comment on "on economic theory of crime / Richard A. Posner -- Crime, kickers, and transaction structures / Jules L. Coleman -- Is there an economic theory of crime? / Stephen J. Schulhoffer